PEER TO PEER LENDING AS ALTERNATIVE ONLINE MICROFINANCE PLATFORM: THREAT AND CHALLENGE TO ISLAMIC MICROFINANCE - Hasyim, Fuad (Indonesian Journal of Islamic Literature and Muslim Society, 2019)
Technological progress will be in line with the development of science. Innovation was created to provide positive benefits and convenience for human life. This study aims to see the public acceptance of the use of online financing applications called P2P Lending. The approach is made by using the Technology Acceptance Model Theory with Structural Equation Modeling (SEM). The results show that all constructs consisting of PEoU, PU, Attitude, Behavior Intention to Use and Actual System Use have a significant effect (α <0.05). The conclusion tells us that convenience will create a positive user experience (useful) so that it has an impact on the attitude of using the P2P lending platform. A continuous attitude will form habits, which will eventually reach a high frequency of use (addiction) and create user satisfaction. At the level of user satisfaction, this means that acceptance from P2P Lending is welcomed and enthusiastic for millennials and has the potential to threaten traditional microfinance (disruptive) like BMT.